Healing of Skin Wounds in Rats: Influence of Low-Level Laser Therapy, Alone or Combined with Natural Products - Maciel, Diana Milanez Ávila Dias; Rahal, Sheila Canevese; Fonseca Alves, Carlos Eduardo; Charas dos Santos, Ivan Felismino; de Abreu Sampaio, Alexandre Botelho; Nagai, Laís Rosa; Duarte Ferraz de Camargo, Barbara Wagner; Salewski, Gabriela Cunha (Acta Scientiae Veterinariae, 2020)
Background: A great variety of natural products have been evaluated for the skin wound healing due to anti-inflammatory, antioxidant and antibacterial activities, and procollagen synthesis, of which may be mentioned the honey and propolis. In turn, low-level laser therapy (LLLT) is considered an important tool in the treatment of skin wounds, because of ability to raise the ATP production, to stimulate the microcirculation, and formation of new blood vessels. Therefore,this study aimed to assess the influence of LLLT, alone or combined with natural products, in the healing of excisional skin wounds in rats. Materials, Methods & Results: One hundred twenty-six male Wistar rats, aged 14 weeks, were randomly divided into seven groups (n = 18 per group) according to wound treatments: G1 (negative control): 0.9% saline solution; G2 (positive control): allantoin + zinc oxide ointment; G3: LLLT; G4: mixture of honey + 5% propolis hydroalcoholic solution; G5: LLLT + honey + hydroalcoholic solution of 5% propolis; G6: LLLT + honey in natura; G7: LLLT + 5% propolis hydroalcoholic solution. Six rats from each group were euthanized on the 7th, 14th, and 21th postoperative days. Macroscopic and histological evaluations of wound healing were performed. A decrease in wound area occurred in all groups, but in general G4 had the higher reduction and G1 and G3 had the lower reductions. These findings corresponded to the percentage of wound contraction, since the largest contraction was G4 and the lowest contractions were G1 and G3. Histological analysis showed no significant difference among groups on the 7th postoperative day. On postoperative day 14, a significant decrease in hemorrhage occurred between G1xG4, G1xG5 and G1xG7, and a significant decrease in congestion between G1xG7 and G2xG5. In addition, intensity of the inflammatory infiltrate showed a significant reduction between G1xG7, G2xG7 and G3xG7. On postoperative day 21, a significant changed from mixed to mononuclear inflammatory infiltrate was observed between G1xG3, G1xG4, G1xG6, G1xG7, G2xG3, and G2xG6. Regarding organization of fibroblasts, there were differences between G1xG6 and G1xG7. Discussion: Spite the red laser has been associated to in increase fibroblast proliferation, G3 showed inadequate decrease in wound area and percentage of contraction. Histological examination showed no differences among groups in the inflammatory phase. However, in the proliferative and remodeling phases around days 14 and 21 were found some differences among groups, which may be related to the actions of the natural products, or laser. Studies have shown that honey acts as a repair and anti-inflammatory agent in skin woundthat may be associated to lower hemorrhage in G4 and G4 compared to G1 on day 14. Propolis is related to reduction of free radicals and increasing the amount of collagen, which may have contributed for quality improvement of the inflammatory infiltrate in G4 and G7 compared to G1, and fibroblast organization in G7 at postoperative day 21. In conclusion, macroscopically the mixture of honey + 5% propolis hydroalcoholic solution was the most effective in reducing wound area and increasing wound contraction. However, based on the parameters evaluated histologically, may be highlighted the evolution of the treatments with LLLT + honey, as well as LLLT + 5% propolis hydroalcoholic solution. Keywords: honey, propolis, biomodulation, wound, healing.